A novel method to fabricate nanoporous gadolinium-doped ceria interlayer by combining wet-etching and thin film deposition. Issue 17 (1st December 2019) - Yu, Wonjong; Lee, Sanghoon; Choi, Inwon; Jeong, Wonyeop; Cho, Gu Young; Cha, Suk Won
Abstract: Fabrication of nanoporous doped ceria thin film by sputtering method has attracted attention for lowering operating temperature of solid oxide fuel cells and enhancing active sites for oxygen reduction reaction (ORR). However, it is difficult to obtain nanoporous structure of doped ceria by sputtering due to deposition characteristic of oxide thin film. A novel method for fabricating 300nm-thickness of nanoporous gadolinium-doped ceria (GDC) interlayer is developed by combining wet-chemical etching and co-sputtering. The nanostructure of thin film Ag-GDC cermet varied with deposition power of Ag and GDC was optimized for cathode interlayer. By etching Ag nanoparticle out of the Ag-GDC cermet interlayer, the highly porous nanostructure of GDC was obtained. The peak power density of the cell with nanoporous GDC interlayer was increased by more than a factor of 2.5 compared to that of the cell without the interlayer. Nanostructure and material properties of the GDC interlayer were analyzed by FESEM, XRD, and XPS.